Implementation of Augmented Reality Technology for the Mobile-Based Introduction of Toraja Traditional Clothes - nfn Rismayani; Novita Sambo Layuk (BBPSDMP KOMINFO MAKASSAR, 2019)
Every region in Indonesia has a traditional clothes that is characteristic of each region, especially the Tanah Toraja that located in the province of South Sulawesi. The Rantepao Art Center building is one of the art buildings located in Tana Toraja, precisely in downtown Rantepao, North Toraja district. The problem is that during this time, the Rantepao art center building only introduces Toraja traditional clothes by means of dialogue, beside of books or catalogs those available there. Efforts are needed on how to present a model of introduction of Toraja traditional clothing and accessories in a more attractive and interactive three-dimensional form. Thus the tourists can easily understand each of the Toraja traditional clothing model and its accessories. We use marker based tracking with Augmented Reality technology. Augmented Reality is a technology that combines marker objects into a real three-dimensional environment and displays them in real time. The results of this study are by displaying three-dimensional images of toraja traditional clothes by using a mobile device to capture images on smartphones, so that visitors of North Toraja regency's art center, both local and international, can see the more attractive appearance of toraja traditional clothes.